Human Impacts on Insect Chemical Communication in the Anthropocene - Knaden, Markus; Anderson, Peter; Andersson, Martin N.; Hill, Sharon R.; Sachse, Silke; Sandgren, Mats; Stensmyr, Marcus C.; Löfstedt, Christer; Ignell, Rickard; Hansson, Bill S. (Frontiers in Ecology and Evolution, 2022)
The planet is presently undergoing dramatic changes caused by human activities. We are living in the era of the Anthropocene, where our activities directly affect all living organisms on Earth. Insects constitute a major part of the world’s biodiversity and currently, we see dwindling insect biomass but also outbreaks of certain populations. Most insects rely on chemical communication to locate food, mates and suitable oviposition sites, but also to avoid enemies and detrimental microbes. Emissions of e.g. CO2, NOx and ozone can all affect the chemical communication channel, as can a rising temperature. Here, we present a review of the present state of the art in the context of anthropogenic impact on insect chemical communication. We concentrate on present knowledge regarding fruit flies, mosquitoes, moths and bark beetles, as well as presenting our views on future developments and needs in this emerging field of research. We include insights from chemical, physiological, ethological and ecological directions and we briefly present a new international research project, the Max Planck Centre for Next Generation Insect Chemical Ecology (nGICE), launched to further increase our understanding of the impact of human activities on insect olfaction and chemical communication.